2007
DOI: 10.1080/09273940701382374
|View full text |Cite
|
Sign up to set email alerts
|

Immune Privilege and Immunogenicity Reside among Different Layers of the Mouse Cornea

Abstract: Purpose: To determine the extent to which each layer of the mouse cornea displays alloimmuno-genicity or immune privilege. Methods: Intact corneas or individual or combined layers of corneas from normal or cauterized eyes of BALB/c, C57BL/6, and CD95L-deficient B6-gld mice were grafted beneath the kidney capsule of normal BALB/c, B10.D2, BALB.B mice or of BALB/c mice presensitized to donor antigens. Graft fate was assessed clinically and histologically and acquisition of donor-specific delayed hypersensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…[18][19][20][21][22][23][24] Numerous basic research studies have demonstrated that the immune privilege of the eye is not solely a phenomenon due to immunologic ignorance, but instead is a highly orchestrated immune system consisting of unique immune suppression mechanisms, widely known as anterior chamber-associated immune deviation. [21][22][23]25 This immuneprivileged environment, as well as the underlying mechanisms involved in corneal graft rejection by host immune systems, has also been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24] Numerous basic research studies have demonstrated that the immune privilege of the eye is not solely a phenomenon due to immunologic ignorance, but instead is a highly orchestrated immune system consisting of unique immune suppression mechanisms, widely known as anterior chamber-associated immune deviation. [21][22][23]25 This immuneprivileged environment, as well as the underlying mechanisms involved in corneal graft rejection by host immune systems, has also been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of reconstituted mouse corneal grafts confirmed that the corneal epithelium had a higher allosensitization potency when compared with endothelium. [35][36][37] By contrast, the incidence of graft rejection in DSEK, and even in DMEK, suggests that the corneal endothelium also has immunogenicity. Our current data for our rabbit DSEK model showed that immune cells migrated onto allogeneic graft corneal endothelium and expressed proinflammatory cytokines, as observed in PK.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parts of the eye like the cornea are considered to be intrinsically immune privileged tissues because when transplanted to sites perfectly capable of rejecting foreign antigens, they enjoy acceptance. For instance, a cornea is accepted when transplanted under the kidney capsule, a site that is not immune privileged [5,6].…”
Section: Regional Specialization Of Immune Responsesmentioning
confidence: 99%
“…In addition, normal corneal endothelial cells constitutively express immune-modulating factors such as CD95L (28). Thus, corneal endothelium is considered to play a central role in the protection of corneal allografts from immunologic rejection when transplanted orthotopically in the eyes (29) and heterotopically beneath the kidney capsule (30,31). Molecular mechanisms of corneal invulnerability are not perfectly understood.…”
mentioning
confidence: 99%